Environmental Sensing: Designing an Efficient Multimode Environmental Sensor Based on Graphene–Silicon Heterojunction (Adv. Mater. Technol. 4/2017). Issue 4 (April 2017) - Shehzad, Khurram; Shi, Tianjin; Qadir, Akeel; Wan, Xia; Guo, Hongwei; Ali, Ayaz; Xuan, Weipeng; Xu, Hua; Gu, Zhongze; Peng, Xinsheng; Xie, Jin; Sun, Litao; et al.
Abstract : In article number1600262, Yang Xu and co‐workers develop an efficient environmental sensing platform by combining an array of Gr/Si Schottky diodes with a differential amplifier circuit. This platform can simultaneously sense and differentiate the environmental elements including temperature, humidity, and the sunlight.